ANALISIS PENGARUH STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI GIANT SUPERMARKET EXPRESS DINOYO MALANG - Prabowo, Fitriansyah Budi; Rahardjo, Toto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims to determine the probability of consumers who make purchasing decisions based on variable exterior, interior general, store layout and interior display at Giant Supermarket Express Dinoyo Malang. This is an explanatory research. The populations in this study are all the consumers of Giant Supermarket Express Dinoyo Malang. The sampling technique was conducted with a purposive sampling method. The technique of data collection in this study carried out on September, 17 2014 using a questionnaire. The validity of the instrument is calculated by Cronbach Alpha coefficient. The data were analyzed using logistic regression analysis. The results showed that (1) the variable exterior has a large probability of the product purchase decisions, (2) general variable interior has a small probability on product purchasing decisions, (3) the variable store layout has a large probability of the product purchase decisions, (4 ) variable interior display has a small probability on product purchasing decisions.Keywords: Store Atmosphere, Purchasing Decisions, Operations.